POTENSI JENIS-JENIS SAGU di DISTRIK KAIS KABUPATEN SORONG SELATAN - Franklin D Paiki; Sri Anggasari Makatita; Krisna Fransina Lermating; Hendry James Yoel Aidore (P3M Politeknik Negeri Ambon, 2022)
This study aims to: (1). determine the diversity of sago species based on morphological characters and kinship levels; (2). determine the growth rate and abundance of sago species found in the Natural Sago Forest (HSA) of Kais District, and (3). knowing the production potential of sago types found in HSA Kais District. The research was conducted for 1 month in September 2022, located in the Natural Sago Forest of Kais District, South Sorong Regency. The research methods used are surveys and field observations. Types of sago taken from sample plots in the study area at the MT level. This study uses the Potential Inventory technique by drawing Line Plot Systematic Sampling or sampling based on pathways. The Base Line that is made cuts the contour lines to make it easier to see the characteristics of vegetation. The results showed that there were 5 types of sago based on the naming of the local naming of the community, namely, Raimamare (sago nipah), Kororo (red sago), Mugici (wild sago or forest sago), Fiaro/Demago (red sago) and Bitafo (planting sago). Mugici and Bitafo have the highest importance index compared to other types. Very dominating because this type of sago is found in all observation plots. The age range of sago trees in the Natural Sago Forest of Kais district ranges from 16.2 years to 36.5 years. The production potential of each type of superior sago is the Kororo type with the traditional extracted wet sago starch production process of 266.8 kg. Keywords: Metroxylon, Potential, Kais, South Sorong